2002
DOI: 10.1021/ac0200116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of Concurrent Gas−Liquid Interfacial Adsorption and Partitioning in Gas−Liquid Chromatography

Abstract: The importance of adsorption at the gas-liquid interface on retention in gas-liquid chromatography has been controversial since the pioneering work of Martin in the 1960s. In particular, experimental studies using chromatographic and static techniques to quantify partitioning and adsorption of polar analytes on nonpolar liquid phases yielded conflicting results. In this work, Monte Carlo simulations were carried out for a free-standing liquid slab of squalane surrounded by a helium vapor to investigate interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
4
33
0
Order By: Relevance
“…[25][26][27][28] As expected, they found that the squalanevapor interface does not appear to be molecularly sharp. Squalane molecules protrude through the interface, and the density profile declines to the vacuum value over a significant distance.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[25][26][27][28] As expected, they found that the squalanevapor interface does not appear to be molecularly sharp. Squalane molecules protrude through the interface, and the density profile declines to the vacuum value over a significant distance.…”
Section: Introductionsupporting
confidence: 64%
“…Simulations were performed using the TraPPE (transferable potential for phase equilibria) force field developed by Siepmann and coworkers. [25][26][27][28] A united atom model was used to describe all the CH 3 , CH 2 , and CH units. All simulations were performed in the NVT ensemble using the program DL_POLY2 on an Intel Xeon 3.0 GHz dual processor workstation.…”
Section: Experimental Technique and Simulation Methodsmentioning
confidence: 99%
“…Figure 1 shows that the density of liquid alkane peaks at about 0.5 nm from that interface. The existence of interfacial density peaks has been previously reported for other alkanes [101,102]. The density peaks are sharper at the nonane-water interface than at the nonane-vacuum interface.…”
Section: Interfacial Orientation Of Liquid Alkanes Is Controlled By Tsupporting
confidence: 64%
“…This method can also be modified in order to study the liquid-liquid equilibria between two immiscible liquids [19,20]. The use of boxes with interface in the Gibbs Ensemble Monte Carlo also represents a powerful technique which enables us to study the properties of interfaces between vapor and saturated solution of two immiscible liquids [21][22][23]. Molecular Dynamics (MD) simulations in such boxes were also used in studying the free surface of alkane oligomers [24][25][26].…”
Section: Introductionmentioning
confidence: 99%